An empirical model of sustainable manufacturing supply chains for enabling a low-carbon economy. (1st January 2013) - So, Stuart
In this study, an empirical model for sustainable supply chain management (SSCM) in an electronically-enabled manufacturing supply chain (EMSC) is proposed for supply chain decarbonisation with the aim to shape a low-carbon economy. A hybrid approach is used which involves: (a) technology acceptance model (TAM) and DeLone and McLean's (D&M) information systems success model in building the concept; (b) supply chain operations reference (SCOR) model in operationalising the variables. The enabling methodology is based on two principles: (a) dematerialisation on major supply chain processes; (b) green logistic distribution adopted for reducing environmental impacts. The model was tested with empirical data obtained from 558 manufacturing firms in 17 countries. The results suggest several key successful factors in the adoption of SSCM that concern organisational readiness, including top management support and individual participation, while the perceived benefits of this new practice is a major adoption decision-making element.